Association Between Basic Immunization Status and Stunting Among Children Under Five: A Multivariate Analysis in a Primary Healthcare Setting - Ratna Roesardhyati; Rafsanjani Rafsanjani (Tarqabin Nusantara Group, 2026)
Stunting remains a persistent public health challenge driven by multifactorial conditions, including infection exposure and suboptimal caregiving practices. Immunization may contribute to stunting prevention through infection control pathways; however, evidence from primary healthcare settings remains limited and methodologically inconsistent. This study aimed to examine the association between basic immunization status and stunting among children under five using a multivariate approach that accounts for key confounding factors. A cross-sectional study was conducted among 120 mothers with children aged 12–59 months in the Wayabula Primary Health Center area. Data were collected using structured questionnaires, verified child health records, and anthropometric measurements. Basic immunization status was treated as the primary exposure, while exclusive breastfeeding, infection history, and household sanitation were included as covariates. Data were analyzed using chi-square tests and multivariate logistic regression to estimate adjusted associations. Incomplete immunization was significantly associated with stunting in bivariate analysis (p=0.012). After adjusting for covariates, children with incomplete immunization had higher odds of stunting (AOR=2.87; 95% CI: 1.31–6.29). Infection history and poor sanitation were also significantly associated with stunting within the model. These findings indicate that immunization status is independently associated with stunting after controlling for key confounding factors. Strengthening immunization coverage within integrated primary healthcare services may contribute to more effective stunting prevention strategies.